2018
DOI: 10.1186/s40643-018-0192-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a yeast old yellow enzyme for highly enantioselective reduction of citral isomers to (R)-citronellal

Abstract: Background: A NAD(P)H-dependent enoate reductase (OYE2p) from Saccharomyces cerevisiae YJM1341 was discovered by genome data mining for asymmetric reduction of (E/Z)-citral to (R)-citronellal with high enantioselectivity. Methods:This enzyme was heterologously expressed in E. coli and characterized for its biocatalytic properties. OYE2p was identified with reduction activities toward a diverse range of ɑ,β-unsaturated compounds bearing conjugated aldehyde, ketone, imide, carboxylic acid and ester.Results: OYE2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 21 publications
2
33
0
Order By: Relevance
“…The time course of ( E / Z )-citral reduction clearly indicated that the ratio of geranial and neral significantly affected the e.e. value of ( R )-citronellal, which was consistent with previous observations [7,14]. In addition, the isomerization of geranial and neral occurred under some conditions [9,30].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The time course of ( E / Z )-citral reduction clearly indicated that the ratio of geranial and neral significantly affected the e.e. value of ( R )-citronellal, which was consistent with previous observations [7,14]. In addition, the isomerization of geranial and neral occurred under some conditions [9,30].…”
Section: Resultssupporting
confidence: 92%
“…Furthermore, the ( Z )-citral-derived e.e. value of R330H (71.92%, R ) was much higher than that of OYE2p (26.5%, R ) [7], suggesting that the role of S13, S59, and V289 could not be ignored for the ( R )-enantioselectivity. For the single substitutions, the ( R )-enantioselectivity improvement in the ( E / Z )-citral reduction was mainly attributed to the enantioselectivity inversion in the ( Z )-citral reduction, meanwhile, the same variant reduced ( E )-citral to ( R )-citronellal with similar e.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strikingly, Ppo-Er1 retained a relative specific activity of >70% at temperatures as low as 10 • C making the enzyme an interesting candidate to be used for the transformation of thermolabile substrates such as aldehydes ( Figure 3). Overall, our Ppo-Er1 data confirm that the temperature profile of class III enzymes resembles those of their mesophilic counterparts of class I, for example NemA [45] with a reported T opt of 30-50 • C and OYE2p [48] with a T opt of 25-40 • C. Finally, we employed the ThermoFAD technique to determine the melting temperature of Ppo-Er1 and found that the ene reductase unfolds at T m = 46.5 ± 1 • C ( Figure S15). The use of cosolvents is often a "must" in biocatalytic processes due to the presence of high concentrations of various organic substrates.…”
Section: Expression and Characterization Of Ppo-er1supporting
confidence: 76%
“…Thus, the optimum temperatures for the investigated class III and IV enzymes are more similar to those of their mesophilic counterparts from class I, for example, 25–40 °C for OYE2p or 30–50 °C for NemA . In contrast, thermophilic‐like class II OYEs, which have an average increased thermal stability compared to class I enzymes, partly exhibit higher optimum temperatures as observed for CrS ( T opt =65 °C) GeoER ( T opt =70 °C) and FOYE1 ( T opt =50 °C) .…”
Section: Resultsmentioning
confidence: 99%